Characteristics of milk production traits of Balkan goats raised under “low-input” production systems - Vladan Bogdanović (Mljekarstvo)
In order to analyse dairy production traits (milk yield in full lactation, milk fat content, daily milk yield and length of lactation) of Balkan goats raised under “low-input” production systems, data on 440 lactation records from 118 does raised on 9 farms in south-east part of Serbia were used. General linear model, used for analysing variability of lactation length, was consisting of following fixed effects: farm, year of birth, year of production and number of lactation. Model for milk yield in full lactation, milk fat content and daily milk yield was consisting of farms, year of birth, year of production and number of lactation as fixed effects and length of lactation as covariate. The highest milk yield (392 kg) and the highest milk fat content (3.89 %) were achieved in III lactation. Effects of farm, year of production and number of lactation were very significant sources of variation (P<0.001) for milk yield, daily milk yield and milk fat content, while the year of birth as factor of phenotypic variation in these traits expressed no such consistency. Highly significant sources of variation (P<0.001) for the length of lactation were farm and year of production, while the length of lactation had a significant influence (P<0.001) only for total milk yield variability.